Lack of association between PRNP 1368 polymorphism and Alzheimer's disease or vascular dementia - Jeong Byung-Hoon; Lee Kyung-Hee; Lee Yun-Jung; Kim Yun; Choi Eun-Kyoung; Kim Young-Hoon; Cho Young-Sook; Carp Richard I; Kim Yong-Sun (BMC, 2009)
Abstract Background Polymorphisms of the prion protein gene (PRNP) at codons 129 and 219 play an important role in the susceptibility to Creutzfeldt-Jakob disease (CJD), and might be associated with other neurodegenerative disorders. Several recent reports indicate that polymorphisms outside the coding region of PRNP modulate the expression of prion protein and are associated with sporadic CJD, although other studies failed to show an association. These reports involved the polymorphism PRNP 1368 which is located upstream from PRNP exon 1. In a case-controlled protocol, we assessed the possible association between the PRNP 1368 polymorphism and either Alzheimer's disease (AD) or vascular dementia (VaD). Methods To investigate whether the PRNP 1368 polymorphism is associated with the occurrence of AD or VaD in the Korean population, we compared the genotype, allele, and haplotype frequencies of the PRNP 1368 polymorphism in 152 AD patients and 192 VaD patients with frequencies in 268 healthy Koreans. Results and conclusion Significant differences in genotype, allele and haplotype frequencies of PRNP 1368 polymorphism were not observed between AD and normal controls. There were no significant differences in the genotype and allele frequencies of the PRNP 1368 polymorphism between Korean VaD patients and normal controls. However, in the haplotype analysis, haplotype Ht5 was significantly over-represented in Korean VaD patients. This was the first genetic association study of a polymorphism outside the coding region of PRNP in relation to AD and VaD.